Fractonic superfluids. II. Condensing subdimensional particles - Shuai A. Chen; Jian-Keng Yuan; Peng Ye (Physical Review Research, 2021)
As a series of work about “fractonic superfluids,” in this paper, we develop an exotic fractonic superfluid phase in d-dimensional space where subdimensional particles—their mobility is partially restricted—are condensed. The off-diagonal long range order (ODLRO) is investigated. To demonstrate, we consider “lineons”—a subdimensional particle whose mobility is free only in certain one-dimensional directions. We start with a d-component microscopic Hamiltonian model. The model respects a higher-rank symmetry such that both particle numbers of each component and angular charge moments are conserved quantities. By performing the Hartree-Fock-Bogoliubov approximation, we derive a set of Gross-Pitaevskii equations and a Bogoliubov–de Gennes (BdG) Hamiltonian, which leads to a description of both condensed components and unification of gapless phonons and gapped rotons. With the coherent-path-integral representation, we also derive the long-wavelength effective field theory of gapless Goldstone modes and analyze quantum fluctuations around classical ground states. The Euler-Lagrange equations and Noether charges/currents are also studied. In two spatial dimensions and higher, such an ODLRO stays stable against quantum fluctuations. Finally, we study vortex configurations. The higher-rank symmetry enforces a hierarchy of thermal vortex excitations whose structures are dominated by two guiding statements. Specially, we construct two types of vortex excitations, the conventional and dipole vortices. The latter carries a charge with dimension as a momentum. The two statements can be more generally applicable. Further perspectives are discussed.